Эмоциональная устойчивость и ее влияние на успешность соревновантельной деятельности спортсменов-спасателей - Komendant С. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
This article investigates the conception of emotional stability as personality characteristic and emotional tension as psychic state of sportsmen-rescuers. The influence of the specified phenomena on doing group exercises is elaborated. The recommendations for emotional tension preventive maintenance which promote emotional stability while doing fire and rescue sport exercises are given